Forecasting sovereign bonds markets using machine learning: forecasting the portuguese government bond using machine learning approach - Vieira, Tiago Alexandre Rodrigues de Sousa (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management